Criminal Law Enforcement On the Role of Social Media in Cases of the Spread of Hoaxes and Slander - Arika, Nur; Aswari, Aan; Saputra, Imran Eka (HORIZON PUBLIC LEGAL STUDIES, 2025)
This study aims to analyze the differences in legal treatment of hoax and defamation dissemination on social media compared to conventional media and to understand the role of social media in preventing the spread of false information. The research adopts an empirical juridical approach by conducting interviews with South Sulawesi Regional Police Crime Investigation Unit . The findings indicate differences in legal treatment based on the characteristics of both types of media, including variations in the sanctions imposed on perpetrators. On social media, preventive measures are carried out through public education, particularly targeting social media users, about the legal risks of spreading hoaxes. South Sulawesi Regional Police Crime Investigation Unit established the Cyber Patrol Task Force as part of its preventive and repressive strategies to tackle the issue